Cultural Foundations of Female Entrepreneurship in Mexico: Challenges and Opportunities - Cantú Cavada, Martha; Bobek, Vito; Skoko, Hazbo; Maček, Anita (Naše gospodarstvo/Our economy, 2018)
This paper analyses possible challenges and opportunities that Mexican female entrepreneurs face during the establishment of new enterprises. Based on in-depth interviews with female entrepreneurs and entrepreneurship experts, authors researched opportunities in the form of governmental and non-governmental institutional support, growing entrepreneurship, social awareness and women empowerment. However, lack of credibility, fear of vulnerability to criticism and social pressure are some challenges associated with gender egalitarianism. In such, the authors proved that Mexican culture impacts women in some ways more than the others. Institutional collectivism was the cultural dimension with higher positive impact on women, followed by gender egalitarianism with a neutral to positive impact and the power distance with a neutral influence on women.
Keywords: female entrepreneurship; culture; Mexico; challenges; opportunities